The impact of prebiotic fructooligosaccharides on gut dysbiosis and inflammation in obesity and diabetes related kidney disease. Issue 11 (18th May 2022) - Pengrattanachot, Nattavadee; Thongnak, Laongdao; Lungkaphin, Anusorn
Abstract : Mechanisms involved in obesity, diabetes and kidney dysfunction via exacerbation of inflammatory response and its association with gut dysbiosis, and role of FOS on improvement of gut dysbiosis and attenuation of inflammation in obesity and diabetes. Abstract : Obesity is an extensive health problem worldwide that is frequently associated with diabetes. It is a risk factor for the development of several diseases including diabetic nephropathy. Recent studies have reported that gut dysbiosis aggravates the progression of obesity and diabetes by increasing the production of uremic toxins in conjunction with gut barrier dysfunction which then leads to increased passage of lipopolysaccharides (LPS) into the blood circulatory system eventually causing systemic inflammation. Therefore, the modification of gut microbiota using a prebiotic supplement may assist in the restoration of gut barrier function and reduce any disturbance of the inflammatory response. In this review information has been compiled concerning the possible mechanisms involved in an increase in obesity, diabetes and kidney dysfunction via the exacerbation of the inflammatory response and its association with gut dysbiosis. In addition, the role of fructooligosaccharides (FOS), a source of prebiotic widely available commercially, on the improvement of gut dysbiosis and attenuation of inflammation on obese and diabetic conditions has been reviewed. The evidence confirms that FOS supplementation could improve the pathological changes associated with obesity and diabetes related kidney disease, however, knowledge concerning the mechanisms involved is still limited and needs further elucidation.